Graffiti, Street Art, Walls, and the Public in Canadian Copyright Law - Chapdelaine, Pascale (2019)
Graffiti is vilified, and at the same time is increasingly revered and celebrated. This ambivalence is reflected in the general legal landscape that surrounds graffiti and other forms of street art at the criminal, civil and municipal levels. Within this general legal framework, the application of copyright law to graffiti and street art reveals a complex web of interwoven issues about the protection of the graffiti artist’s economic and moral rights and questions of illegality and public policy, and about the rights of the property owner of the “wall” on which the art resides, and the public. This book chapter explores how the law mediates between the rights of graffiti and street artists, the rights of the property owner on which the art resides, and members of the public. The application of copyright law to graffiti and street art offers an opportunity to investigate where the balance should lie between various competing rights and interests relating to these types of works.
Keywords: Pascale Chapdelaine